Obesity, Insulin Resistance, and Incident Small Vessel Disease on Magnetic Resonance Imaging: Atherosclerosis Risk in Communities Study. Issue 11 (November 2015) - Dearborn, Jennifer L.; Schneider, Andrea L.C.; Sharrett, A. Richey; Mosley, Thomas H.; Bezerra, Daniel C.; Knopman, David S.; Selvin, Elizabeth; Jack, Clifford R.; Coker, Laura H.; Alonso, Alvaro; Wagenknecht, Lynne E.; Windham, Beverly G.; et al.
Abstract : Background and Purpose—: The term metabolic syndrome describes the clustering of risk factors found in many individuals with obesity. Because of their pathophysiology, we hypothesized that 2 features of metabolic syndrome, central obesity and insulin resistance (IR), would be associated with cerebrovascular changes on magnetic resonance imaging, and specifically with incident lacunar disease and not white matter hyperintensity (WMH) progression. Methods—: Risk factors were defined at study baseline in 934 participants in the Atherosclerosis Risk in Communities (ARIC) study, who completed 2 brain magnetic resonance imagings ≈10 years apart. WMH progression and incident lacunes between the 2 magnetic resonance imagings were determined. An IR score for each participant was created using principal component analysis of 11 risk factors, including (among others): insulin, homeostatic model assessment-IR, body mass index, and waist circumference. Metabolic syndrome (presence/absence), using standard clinical definitions, and IR score at the first magnetic resonance imaging, were independent variables, evaluated in multivariate logistic regression to determine odds of WMH progression (Q5 versus Q1–Q4) and incident lacunes. Results—: Metabolic syndrome (adjusted odds ratio, 1.98; 95% confidence interval, 1.28–3.05) and IR score (adjusted odds ratio per 1-SD increase, 1.33; 95% confidence interval, 1.05–1.68) were associated with incident lacunes but not with WMH progression. Insulin, homeostatic model assessment-IR, and body mass index were not associated with incident lacunes or WMH progression in separate models. Conclusions—: The IR score and central obesity are associated with incident lacunar disease but not WMH progression in individuals. Central obesity and IR may be important risk factors to target to prevent lacunar disease. Abstract : Supplemental Digital Content is available in the text.